Integrative Combat: An Empirical Perspective of the Martial Arts - Gregory Vey (Universidad de León, 2012)
There have been many past efforts to define the martial arts and to render them in a pseudoscientific manner. The present work attempts to delineate a subset of the greater entity of the martial arts that is primarily concerned with combat as an observable, measurable, and testable phenomenon. The term Integrative Combat (IC) is proposed here to denote such a research area. Applying the tenets of empirical reductionism, a model for IC is proposed that consists of three layers of conceptual abstraction. The IC model offers a means to envision scientific research on combat and to illustrate the benefits of interconnectivity between diverse research interests undertaken from varying levels of conceptual complexity. By forging a scientific approach to the martial arts it becomes possible to achieve new heights of technical knowledge and combative expertise. Thus, IC has the potential to emerge as its own powerful and legitimate field of study.